2022
DOI: 10.1128/spectrum.01006-21
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of Transition Metals on Growth and Metal Uptake for Two DistinctLactobacillusSpecies

Abstract: The gastrointestinal tract contains trillions of microorganisms, which are central to human health. Lactobacilli are considered beneficial microbiota members and are often used in probiotics, but their molecular functions, and especially those which are metal-dependent, remain poorly defined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 133 publications
0
11
0
Order By: Relevance
“…Even for MRS (control), the specific speeds of 0,15 h -1 and generation time of 1,37 h described have been exceeded (Śliżewska & Chlebicz-Wójcik, 2020). In previous studies, specific speeds ranging from 0,23 to 0,73 h -1 and latency times from 2,89 to 4,4 h have been reported (Hang et al, 2020;Huynh et al, 2022;Rocha-Mendoza et al, 2020). In these studies, the differences in the parameters have been attributed to the availability of sugars in culture media (Alemneh et al, 2021).…”
Section: Effect Of Ae On the Growth Of L Plantarum And L Acidophilusmentioning
confidence: 81%
See 1 more Smart Citation
“…Even for MRS (control), the specific speeds of 0,15 h -1 and generation time of 1,37 h described have been exceeded (Śliżewska & Chlebicz-Wójcik, 2020). In previous studies, specific speeds ranging from 0,23 to 0,73 h -1 and latency times from 2,89 to 4,4 h have been reported (Hang et al, 2020;Huynh et al, 2022;Rocha-Mendoza et al, 2020). In these studies, the differences in the parameters have been attributed to the availability of sugars in culture media (Alemneh et al, 2021).…”
Section: Effect Of Ae On the Growth Of L Plantarum And L Acidophilusmentioning
confidence: 81%
“…L. plantarum exhibited a velocity of 0,136 h -1 at 35 °C indicating that the specific speed decreases when the temperature varies (Canci et al, 2022). On the other hand, although for L. acidophilus there was no improvement in kinetic parameters with AEs, the values in MRS were comparable with latency times of 3,4 to 4 h and speeds of 0,25 to 0,29 h -1 (Huynh et al, 2022). Other studies have reported a specific rate for MRS from 0,05 to 0,11 h -1 and a latency time from 3,14 to 5,3 h (Kolev et al, 2022).…”
Section: Effect Of Ae On the Growth Of L Plantarum And L Acidophilusmentioning
confidence: 92%
“…Despite having similar total quantities of metals in cMRS, B1.3 still contained lower amounts of magnesium, aluminum, and calcium compared to strain B1.1. Presently, aside from a few reports suggesting different metal requirements for lactobacilli (27)(28)(29)(30)(31), the importance of metals for LAB growth and ecological interactions are not well understood. The requirement of L. plantarum for manganese has been specifically investigated (30,32), likely because L. plantarum has a high requirement for Mn 2+ compared to other bacteria and Mn 2+ is known to confer resistance against oxidative (33,34) and heat (35) stress.…”
Section: Discussionmentioning
confidence: 99%
“…Despite having similar total quantities of metals in cMRS, B1.3 still contained smaller amounts of magnesium, aluminum, and calcium than did strain B1.1. Presently, aside from a few reports suggesting different metal requirements for lactobacilli ( 27 31 ), the importance of metals for LAB growth and ecological interactions is not well understood. L. plantarum manganese requirements have been specifically investigated ( 30 , 32 , 33 ), likely because L. plantarum contains elevated levels of Mn 2+ compared to other bacteria and because this element is known to confer resistance against oxidative ( 34 , 35 ) and heat ( 36 ) stress.…”
Section: Discussionmentioning
confidence: 99%